Run-off Patterns of Vancomycin Resistant Enterococci (VRE clones) in Cows Raw Milk and Imported Milk Powders at Baghdad Markets - Al-Shammary, Ali Hassan Ahmed (The Iraqi Journal of Veterinary Medicine, 2019)
Codebook shifting of some clones of Enterococci from normal flora to genotypically and phenotypically foodborne opportunistic and multidrug resistant pathogens in our ecosystem represent dangerous hygienic problem. Seventy-fivepooled milk samples were collectedfrom differentdistricts in Baghdad ecosystem from January until May (2019). Fiftyraw milk samples pooled directly from Cows and milk containers (twenty-five each) and twenty-five imported milk powders pooled from Baghdad markets in which, fifteen samples inspected monthly(five from each brand). Certifiedand modified traitsprofits for isolation and confirmation policy. Frequency and distribution of verified data in Baghdad environment reveled variable results. Seven Enterococcus faecalis phenotypes (9.33 %) recovered from raw milk samples in which, four isolates (5.33 %) recovered from Cows raw milk and three isolates (4 %) recovered from milk containers. None recovered clones founds in imported milk powders. All isolates were biofilm-producers and vancomycin resistant verifiedvia modified Christensen biofilm assay and antibiotics sensitivity test. Monitoring these contamination events with vancomycin resistant Enterococcus faecalis needs sophisticated hygienic efforts in Baghdad ecosystem